2009
DOI: 10.2967/jnumed.109.065193
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction in Diabetic Patients with Abnormal Myocardial Perfusion in the Absence of Epicardial Obstructive Coronary Artery Disease

Abstract: In patients with diabetes mellitus, myocardial perfusion defects are often observed in the absence of obstructive epicardial coronary artery disease (CAD), thereby presenting a diagnostic problem. We hypothesized that these perfusion abnormalities may be explained by endothelial dysfunction or occult coronary atherosclerosis. Methods: Prospectively, 130 asymptomatic patients with diabetes mellitus underwent cardiovascular screening by coronary artery calcium (CAC) scoring, multislice CT coronary angiography, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
2
8
0
3
Order By: Relevance
“…This is consistent with previous findings using nuclear imaging techniques that demonstrate the effects of endothelial dysfunction on myocardial perfusion [27][28][29][30][31]. In particular, Djaberi et al [28] reported regional perfusion defects on adenosine-MPS in 32% of 95 diabetic patients without obstructive CAD on multislice CT angiography that were associated with abnormal brachial artery flowmediated dilation. Storto et al [30] and Marini et al [27] also found, using dipyridamole MPS, homogeneously impaired vascular function in diabetic patients, showing regional perfusion defects in about 30% of them.…”
Section: Myocardial Perfusionsupporting
confidence: 86%
“…This is consistent with previous findings using nuclear imaging techniques that demonstrate the effects of endothelial dysfunction on myocardial perfusion [27][28][29][30][31]. In particular, Djaberi et al [28] reported regional perfusion defects on adenosine-MPS in 32% of 95 diabetic patients without obstructive CAD on multislice CT angiography that were associated with abnormal brachial artery flowmediated dilation. Storto et al [30] and Marini et al [27] also found, using dipyridamole MPS, homogeneously impaired vascular function in diabetic patients, showing regional perfusion defects in about 30% of them.…”
Section: Myocardial Perfusionsupporting
confidence: 86%
“…In the recent years the presence of diabetes has been recognized as a cardiovascular disease (CVD) equivalent and represents for sure a major indication for further cardiovascular risk assessment in these patients (19,20).…”
Section: -Multislice Ct and Calcium Scoring In Diabetesmentioning
confidence: 99%
“…In asymptomatic diabetic patients, stress-induced myocardial ischemia has been widely identified by radionuclide imaging. [ 4 6 ] Nevertheless, the issue of myocardial perfusion changes at rest in these patients remains disputable. Djaberi et al [ 4 ] proved that abnormal myocardial perfusion in diabetic patients without obstructive epicardial CAD was associated with endothelial dysfunction, and also proposed myocardial hypoperfusion may occur during rest.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 6 ] Nevertheless, the issue of myocardial perfusion changes at rest in these patients remains disputable. Djaberi et al [ 4 ] proved that abnormal myocardial perfusion in diabetic patients without obstructive epicardial CAD was associated with endothelial dysfunction, and also proposed myocardial hypoperfusion may occur during rest. However, a single-photon emission computed tomography (SPECT) research demonstrated normal resting myocardial perfusion in T2DM patients without CAD.…”
Section: Introductionmentioning
confidence: 99%